The Law Enforcement against Justice of Criminal Thicking - Nurokhid Nurokhid; Achmad Sulchan (Law Development Journal, 2021)
The purpose of this research is to find out and analyze law enforcement against the perpetrators of criminal theft in Kendal Police, to analyze the factors that influence law enforcement against perpetrators of criminal acts of theft at Polresrang, obstacles that arise in the process of enforcing criminal acts of theft at the Police. Kendal with justice and efforts to overcome it the approach method used is sociological juridical method, the specification in this research is descriptive analytical. The results of the research are that in carrying out law enforcement refers to the Criminal Procedure Code and the Criminal Code and the National Police Perkap No. 6 of 2019 concerning criminal investigation, and Perma No. 2 of 2012 regarding the adjustment of the limitations of minor crimes and the amount of fines in the Criminal Code, the application of criminal acts against theft. Factors affecting law enforcement against the perpetrators of criminal theft at the Kendal Police are just. The obstacles faced are slow reports from the public to the authorities, damage to the crime scene/crime scene, lack of awareness of the public to be witnesses, lack of personnel from members of the police in conducting investigations, lack of necessary facilities and infrastructure such as less sophisticated equipment.